Rescue of infralimbic mGluR2 deficit restores control over drug-seeking behavior in alcohol dependence - Meinhardt, Marcus W; Hansson, Anita C; Perreau-Lenz, Stephanie; Bauder-Wenz, Christina; Stählin, Oliver; Heilig, Markus; Harper, Clive; Drescher, Karla U; Spanagel, Rainer; Sommer, Wolfgang H (The Journal of neuroscience, 2013)
A key deficit in alcohol dependence is disrupted prefrontal function leading to excessive alcohol seeking, but the molecular events underlying the emergence of addictive responses remain unknown. Here we show by convergent transcriptome analysis that the pyramidal neurons of the infralimbic cortex are particularly vulnerable for the long-term effects of chronic intermittent ethanol intoxication. These neurons exhibit a pronounced deficit in metabotropic glutamate receptor subtype 2 (mGluR(2)). Also, alcohol-dependent rats do not respond to mGluR(2/3) agonist treatment with reducing extracellular glutamate levels in the nucleus accumbens. Together these data imply a loss of autoreceptor feedback control. Alcohol-dependent rats show escalation of ethanol seeking, which was abolished by restoring mGluR(2) expression in the infralimbic cortex via viral-mediated gene transfer. Human anterior cingulate cortex from alcoholic patients shows a significant reduction in mGluR(2) transcripts compared to control subjects, suggesting that mGluR(2) loss in the rodent and human corticoaccumbal neurocircuitry may be a major consequence of alcohol dependence and a key pathophysiological mechanism mediating increased propensity to relapse. Normalization of mGluR(2) function within this brain circuit may be of therapeutic value.